Causes of Delay in Construction Projects In Abu Dhabi - ur Rehman, Ghias (2015)
Construction projects experience delays in their completion due to various reasons in the world and United Arab Emirates (UAE) is no exception. Once a project is delayed, it has a negative impact on the concerned parties. Projects being completed on time and handed over is recorded as a performance indicator from technical and commercial point of view. This dissertation aims to makes an in-depth evaluation for the causes of delay in construction projects in Abu Dhabi and rank them to know their importance and consequences. Detailed literature review was carried out and a list of delays was concluded which was further divided into associated groups of the project. Survey questionnaire was developed from the list and used for further evaluation. All associated stakeholders (client, consultants, project managers, contractors, authorities) in the project can be the reason for delay. Some delays are compensated whereas some are not depending on the type of delays. Quantitative research approach is applied in this study conducting a survey from stakeholders. Report analysis shows that the top ten (10) cause of delay based on the ranking are 1) Lack of coordination with Electro Mechanical works, 2) Selection of the lowest bidder commercially, 3) Delay in approvals and late decision making, 4) Material delivery delays, 5) Client introduction of additional works during construction stage, 6) Inefficient planning and scheduling of the projects, 7) Labor and equipment non productivity, 8) Coordination issues and quality of works, 9) Delay in design approvals by Client and 10) Original contract duration is not realistic. A limitation to this dissertation was that there were 61 respondents whereas a larger number of respondents can give a bigger perspective. It was concluded through this dissertation study that project team, owners and contractor factors were the key reasons for delay and if they take responsibility of their action on time, coordinate and work as team they can have successful projects with minimal or no delay.